PERAN SERTA DOSEN DAN MAHASISWA MEMBANGUN KOLABORASI AKADEMIK MELALUI ACARA PROGRAM RISET UNGGULAN PERGURUAN TINGGI - Prawirawati, Ratih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The Featured Research Presentation Program for Higher Education Institutions in Southwest Papua is a strategic initiative aimed at strengthening the implementation of the three pillars of higher education, particularly community engagement through research-based approaches. This article aims to describe the participation of lecturers and students in the program and analyze its impact on community development and academic capacity building. Using a descriptive-qualitative approach, data were collected through participatory observation, documentation, and informal interviews. The findings show that the program successfully featured more than 25 research presentations covering various fields, including appropriate technology, education, public health, and local resource development. Students actively participated as moderators, note-takers, and documentation teams, gaining both academic and practical experience. The forum strengthened inter-institutional academic networks and fostered a collaborative culture that responds to local needs. Presentations from national academic figures enriched participants’ understanding of research as a tool for social transformation, especially in underdeveloped, frontier, and outermost (3T) regions. The forum also produced strategic recommendations for sustainable regional research development. In conclusion, the program serves as an effective model of academic synergy, enhancing the relevance and impact of research on society and empowering students as agents of change through knowledge-based contributions. ABSTRAKProgram Paparan Riset Unggulan Perguruan Tinggi di Papua Barat Daya merupakan inisiatif strategis dalam mendukung penguatan tridharma perguruan tinggi, khususnya pengabdian kepada masyarakat berbasis riset. Artikel ini bertujuan mendeskripsikan partisipasi dosen dan mahasiswa dalam kegiatan tersebut serta menganalisis dampaknya terhadap pembangunan masyarakat dan pengembangan kapasitas akademik. Menggunakan pendekatan deskriptif-kualitatif, data dikumpulkan melalui observasi partisipatif, dokumentasi, dan wawancara informal. Hasil penelitian menunjukkan bahwa kegiatan ini berhasil menjaring lebih dari 25 hasil penelitian yang mencakup berbagai bidang, seperti teknologi tepat guna, pendidikan, dan kesehatan masyarakat, serta melibatkan aktif mahasiswa dalam peran strategis. Forum ini tidak hanya memperkuat jejaring akademik lintas institusi, tetapi juga membangun budaya kolaboratif yang responsif terhadap kebutuhan lokal. Paparan tokoh akademik nasional memperkaya perspektif peserta mengenai pentingnya riset sebagai instrumen perubahan sosial, terutama di wilayah 3T. Selain itu, kegiatan ini menghasilkan rekomendasi strategis untuk penguatan riset berkelanjutan di tingkat regional. Dapat disimpulkan bahwa Program Paparan Riset Unggulan mampu menjadi model sinergi akademik yang efektif dalam meningkatkan relevansi dan dampak riset terhadap masyarakat, serta memperkuat peran mahasiswa sebagai agen perubahan berbasis ilmu pengetahuan.